COMPARATIVE CHARACTERISTICS OF EDUCATIONAL SOFTWARE FOR LEARNING AT HIGHER EDUCATIONAL INSTITUTIONS - Yuliya Slovynska; Anatoliy Franovskyy; Stanislav Mykhaylenkо (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The importance of the educational software training implementation in the modernization of Ukrainian educational system has been proved in the article. The concept of "educational software for learning" has been analyzed and an attempt to summarize and clarify it has been made. Appropriateness of the use of educational software in the preparation of future computer science teachers has been grounded. The comparative characteristics of the existing educational software from the point of view of didactic and functional perspectives have been carried out. A set of electronic applications Gran (Gran1, Gran-2D, Gran-3D) has been investigated and the necessity of their use in higher educational institutions has been proved. The benefits of using educational software training for would-be computer science teachers in their future professional and educational activities have been outlined.